2021
DOI: 10.1002/advs.202100074
|View full text |Cite
|
Sign up to set email alerts
|

HOCl‐Activated Aggregation of Gold Nanoparticles for Multimodality Therapy of Tumors

Abstract: Tumor microenvironment-responsive nanodrugs offer promising opportunities for imaging-guided precision therapy with reduced side effects. Considering that the antitumor effect is closely related to the size of the nanodrugs, it is particularly important to develop a therapeutic system with size adjustability in the tumor microenvironment, which is still a great challenge in the field of nanotheranostics. Herein, a reactive oxygen species (ROS)-activated aggregation strategy is reported for imaging-guided preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…reported a GNP‐based nanoplatform that exploits the higher concentration of HOCl in the tumor microenvironment. [ 285 ] The FDOCl‐24 and PEG conjugated GNPs yield methylene blue (MB) in the presence of HOCl which later can be used as PS to induce PDT. In the process of generating PS, the gold nanoparticle system aggregates which result in a redshift to the NIR region, activating photoacoustic image (PAI) guided PTT and PDT therapy (Figure 18).…”
Section: Gnps Based Improved Therapeuticsmentioning
confidence: 99%
See 3 more Smart Citations
“…reported a GNP‐based nanoplatform that exploits the higher concentration of HOCl in the tumor microenvironment. [ 285 ] The FDOCl‐24 and PEG conjugated GNPs yield methylene blue (MB) in the presence of HOCl which later can be used as PS to induce PDT. In the process of generating PS, the gold nanoparticle system aggregates which result in a redshift to the NIR region, activating photoacoustic image (PAI) guided PTT and PDT therapy (Figure 18).…”
Section: Gnps Based Improved Therapeuticsmentioning
confidence: 99%
“…Due to ease of functionalization for increased cellular uptake as well as PS conjugation, various studies reported PS conjugated GNPs based PDT platform for dual PDT and PTT therapy for cancer treatment. [284,285] Liu et al reported a GNP-based nanoplatform that exploits the higher concentration of HOCl in the tumor microenvironment. [285] The FDOCl-24 and PEG conjugated GNPs yield methylene blue…”
Section: Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Photodynamic therapy (PDT) and photothermal therapy (PTT) have been extensively studied for minimally invasive tumor treatment. [5][6][7] However, since the penetration depth of light waves into the human body is less than 10 mm, 8 these methods have only certain effects on superficial tumors, which limit their effects to treat cervical cancer and its metastases at different FIGO stages. In addition, nanomedicines for PDT or PTT cannot penetrate deep into the tumor.…”
Section: Introductionmentioning
confidence: 99%